SLC35A2‐CDG: Functional characterization, expanded molecular, clinical, and biochemical phenotypes of 30 unreported Individuals. Issue 7 (24th April 2019) - Ng, Bobby G.; Sosicka, Paulina; Agadi, Satish; Almannai, Mohammed; Bacino, Carlos A.; Barone, Rita; Botto, Lorenzo D.; Burton, Jennifer E.; Carlston, Colleen; Chung, Brian Hon‐Yin; Cohen, Julie S.; Coman, David; et al.
Abstract: Pathogenic de novo variants in the X‐linked gene SLC35A2 encoding the major Golgi‐localized UDP‐galactose transporter required for proper protein and lipid glycosylation cause a rare type of congenital disorder of glycosylation known as SLC35A2‐congenital disorders of glycosylation (CDG; formerly CDG‐IIm). To date, 29 unique de novo variants from 32 unrelated individuals have been described in the literature. The majority of affected individuals are primarily characterized by varying degrees of neurological impairments with or without skeletal abnormalities. Surprisingly, most affected individuals do not show abnormalities in serum transferrin N‐glycosylation, a common biomarker for most types of CDG. Here we present data characterizing 30 individuals and add 26 new variants, the single largest study involving SLC35A2‐CDG. The great majority of these individuals had normal transferrin glycosylation. In addition, expanding the molecular and clinical spectrum of this rare disorder, we developed a robust and reliable biochemical assay to assess SLC35A2‐dependent UDP‐galactose transport activity in primary fibroblasts. Finally, we show that transport activity is directly correlated to the ratio of wild‐type to mutant alleles in fibroblasts from affected individuals.